Cross‐Sex Hormonal Treatment and Body Uneasiness in Individuals with Gender Dysphoria. (1st March 2014) - Fisher, Alessandra D.; Castellini, Giovanni; Bandini, Elisa; Casale, Helen; Fanni, Egidia; Benni, Laura; Ferruccio, Naika; Meriggiola, Maria Cristina; Manieri, Chiara; Gualerzi, Anna; Jannini, Emmanuele; Oppo, Alessandro; et al.
Abstract: Introduction: Cross‐sex hormonal treatment (CHT) used for gender dysphoria (GD) could by itself affect well‐being without the use of genital surgery; however, to date, there is a paucity of studies investigating the effects of CHT alone. Aims: This study aimed to assess differences in body uneasiness and psychiatric symptoms between GD clients taking CHT and those not taking hormones (no CHT). A second aim was to assess whether length of CHT treatment and daily dose provided an explanation for levels of body uneasiness and psychiatric symptoms. Methods: A consecutive series of 125 subjects meeting the criteria for GD who not had genital reassignment surgery were considered. Main Outcome Measures: Subjects were asked to complete the Body Uneasiness Test (BUT) to explore different areas of body‐related psychopathology and the Symptom Checklist‐90 Revised (SCL‐90‐R) to measure psychological state. In addition, data on daily hormone dose and length of hormonal treatment (androgens, estrogens, and/or antiandrogens) were collected through an analysis of medical records. Results: Among the male‐to‐female (MtF) individuals, those using CHT reported less body uneasiness compared with individuals in the no‐CHT group. No significant differences were observed between CHT and no‐CHT groups in the female‐to‐male (FtM) sample. Also, no significant differences in SCL score were observed with regard to gender (MtF vs. FtM), hormone treatment (CHT vs. no‐CHT), or the interaction of these two variables. Moreover, a two‐step hierarchical regression showed that cumulative dose of estradiol (daily dose of estradiol times days of treatment) and cumulative dose of androgen blockers (daily dose of androgen blockers times days of treatment) predicted BUT score even after controlling for age, gender role, cosmetic surgery, and BMI. Conclusions: The differences observed between MtF and FtM individuals suggest that body‐related uneasiness associated with GD may be effectively diminished with the administration of CHT even without the use of genital surgery for MtF clients. A discussion is provided on the importance of controlling both length and daily dose of treatment for the most effective impact on body uneasiness.